2020
DOI: 10.1002/cam4.2919
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐320a inhibits invasion and metastasis in osteosarcoma by targeting cytoplasmic polyadenylation element‐binding protein 1

Abstract: Osteosarcoma is a primary malignant bone tumor, which affects children, adolescents, and young adults commonly. MicroRNAs (miRNAs) have been proved to be dysregulated in different cancers, including osteosarcoma. Although miR‐320a has been implicated in many types of malignancies, little is known about the role of miR‐320a in osteosarcoma. In this study, we show that the overexpression of miR‐320a or knockdown of cytoplasmic polyadenylation element‐binding protein 1 (CPEB1) inhibited osteosarcoma cell migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…miR-320a, which is an extensively studied miRNA, has been reported to serve a critical role in diabetic retinopathy (31) and atherosclerosis (32). Moreover, miR-320a has been investigated in several types of cancer, such as lung cancer (33), papillary thyroid cancer (34), osteosarcoma (35) and hepatocellular carcinoma (36). Moreover, miR-320a has been reported to be upregulated in retinoblastoma tissues (37); however its role and mechanism in retinoblastoma remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…miR-320a, which is an extensively studied miRNA, has been reported to serve a critical role in diabetic retinopathy (31) and atherosclerosis (32). Moreover, miR-320a has been investigated in several types of cancer, such as lung cancer (33), papillary thyroid cancer (34), osteosarcoma (35) and hepatocellular carcinoma (36). Moreover, miR-320a has been reported to be upregulated in retinoblastoma tissues (37); however its role and mechanism in retinoblastoma remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that miRNA regulatory networks played an essential effect on the progression and chemoresistance of cancer [ 32 , 33 ]. Liu et al showed that miR-497-5p enhanced apoptosis in OC cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-320a was described as a tumor suppressor for osteosarcoma [9,11] and involved in osteoporotic bone [13], but its effect has never been compared between both cellular contexts. Hence, we overexpressed or inhibited miR-320a in two osteosarcoma cell lines, and the miRNA effects on these two cells lines were compared to that on primary hOBs.…”
Section: Discussionmentioning
confidence: 99%
“…This miRNA was also detected in serums as a circulating microRNA, and it was proposed as a potential biomarker for osteonecrosis of femoral head [5]. Moreover, this miRNA is mainly involved in cancer malignancies including osteosarcoma, in which it acts as a tumor suppressor [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%